Światopogląd a błąd konfirmacji – problem nauk społecznych - Grunt-Mejer, Katarzyna (Filozofia Nauki, 2017)
The work aims to describe the ideological monoculture in social sciences as a source of accumulation of distortion in the description of reality, resulting from a confirmation bias in its several variants (determination of the specific research problem, biased selection of literature, tendentious interpretation of the results, and acceptance of phantom facts in the scientific discourse). Methods of reducing the bias are presented.